Synthesis, Antiviral, and Antimicrobial Evaluation of Benzyl Protected Diversified C-nucleosides - Bari, Ahmed; Ali, Syed S.; Alanazi, Amer M.; Mashwani, Muhammad A.; Al-Obaid, Abdulrahman M. (Frontiers in Chemistry, 2018)
Formyl glycals are the versatile synthetic intermediates and can serves as precursor for the synthesis of various C and N-nucleosides. Due to the presence of electron donating and electron withdrawing character on formyl sugars which makes the molecule more susceptible to nucleophilic attack. Utilizing same strategy, we propose the synthesis of diversified C-nucleosides (3-14) by reaction with N,N dinucleophiles. These nucleoside analogs were than tested against viral, bacterial and fungal strains.